2013
DOI: 10.1107/s0108270113004484
|View full text |Cite
|
Sign up to set email alerts
|

A clothes-peg-shaped binucleartrans-bis(2-aminotroponato)palladium(II) complex bearing pentamethylene spacers

Abstract: rac-Bis{μ-trans-2,2'-[pentane-1,5-diylbis(azanediyl)]ditroponato}dipalladium(II), [Pd2(C19H20N2O2)2], has been synthesized and fully characterized using single-crystal X-ray diffraction, (1)H NMR, FT-IR and mass spectroscopy. The trans coordination, vaulted structure and anti conformation have been unequivocally established from the X-ray diffraction studies. This is the first example of a bis(aminotroponato)palladium complex. In the crystalline state, the molecule has twofold symmetry and each molecular unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…An intermolecular offset -stacking between the C15-C20 phenyl ring of the quinazoline system and the C8-C13 chlorophenyl ring [the centroid of the chlorophenyl ring stacks above atoms C15 ix and C16 ix ; with atom-to-centroid distances of 3.636 (11) and 3.602 (14) Å , respectively; symmetry code: (ix) x À 1, y, z] assists the close packing of the translationally related lapatinib cations along the a axis. A similar observation was noted previously (Komiya et al, 2013;Krause et al, 2013) and it was also suggested by Janiak (2000) that such an arrangement is indicative of a possible -attraction.…”
Section: Figuresupporting
confidence: 87%
“…An intermolecular offset -stacking between the C15-C20 phenyl ring of the quinazoline system and the C8-C13 chlorophenyl ring [the centroid of the chlorophenyl ring stacks above atoms C15 ix and C16 ix ; with atom-to-centroid distances of 3.636 (11) and 3.602 (14) Å , respectively; symmetry code: (ix) x À 1, y, z] assists the close packing of the translationally related lapatinib cations along the a axis. A similar observation was noted previously (Komiya et al, 2013;Krause et al, 2013) and it was also suggested by Janiak (2000) that such an arrangement is indicative of a possible -attraction.…”
Section: Figuresupporting
confidence: 87%
“…However, these materials have not yet been studied sufficiently, owing to the deleterious effects of intermolecular interactions . As part of our program aimed at developing new functional materials based on square planar d 8 transition metal platforms bearing three‐dimensional (3D) superstructures, we are investigating the association/aggregation properties, and molecular mobilities[6c], of chiral clothespin‐shaped binuclear complexes comprising trans ‐bis(salicylaldiminato), and trans ‐bis(aminotroponato) Pd(II)[6a], [6c], [6d], [6e], , and Pt(II)[6b], [6d] complexes doubly linked with flexible or rigid carbon bridges. These clothespin‐shaped complexes exhibit various association and aggregation motifs due to the conformational variation arising from the opening and closing anisotropic flapping motions of the cofacial coordination blades.…”
Section: Introductionmentioning
confidence: 99%
“…A number of vaulted complexes with various tether-linked bidentate ligands [3][4][5][6][7][8][9][10][11][12][13][14] have been synthesized and studied with regard to their inclusion properties [3a-d, 4,5d], molecular aggregation [6a,b], optical properties [3e,f,6b-h], rotation properties as molecular gyroscopes [2,13] and catalytic activities for organic transformations [1,3g-m,11a,12]. As part of our program aimed at the creation of new organometallic functional materials [6a-c], we recently found that polymethylene-and polyoxyethylene-vaulted trans-bis(salicylaldiminato)platinum(II) complexes exhibit significant phosphorescent emission in the crystalline state [6d-h].…”
Section: Introductionmentioning
confidence: 99%